Critical geographies and the uses of sexuality: deconstructing queer space - Oswin, Natalie (Progress in Human Geography, 2008)
Scholarship on queer geographies has called attention to the active production of space as heterosexualized and has levelled powerful critiques at the implicit heterosexual bias of much geographical theorizing. As a result, critical geographers have begun to remark upon the resistance of gays, lesbians and other sexual subjects to a dominant heterosexuality. But such a liberal framework of oppression and resistance is precisely the sort of mapping that poststructuralist queer theory emerged to write against. So, rather than charting the progress of queer geographies, this article offers a critical reading of the deployment of the notion of `queer space' in geography and highlights an alternative queer approach that is inseparable from feminist, materialist, postcolonial and critical race theories.
Keywords: LGBTQIA2+; approches et analyses; architecture; cours; discipline; espace; géographie; hétéronormativité; premier cycle; queer; résistance; sciences humaines; soc2014; thématiques

Mapping desire: geographies of sexualities - Bell, David; Valentine, Gill (Routledge, 1995)
This is the first book to explore sexualities from a geographical perspective. The nature of place and notions of space are of increasing centrality to cultural and social theory. Mapping Desire presents the rich and diverse world of contemporary sexuality, exploring how the heterosexual body has been appropriated and resisted on the individual, community and city scales. The geographies presented here range across Europe, America, Australasia, Africa, the Pacific and the imaginary, cutting across city and country and analysing the positions of gay men, lesbians, bisexuals and heterosexuals. The contributors ring different interests and approaches to bear on theoretical and empirical material from a wide range of sources. The book is divided into four sections: cartographies/identities; sexualised spaces: global/local; sexualised spaces: local/global; sites of resistance. Each section is separately introduced. Beyond the bibliography, an annotated guide to further reading is also provided to help the reader map their own way through the literature.
Le texte de Binnie, Jon. 1995. « Trading places : consumption, sexuality and the production of queer space. » figure dans la bibliographie du cours SOC2014.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; géographie; hétéronormativité; hétérosexisme; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques